Stigma and Discrimination against People Living With Hiv and Aids in The Jaman North District of Brong Ahafo Region - Abudu, E.A. (University of Ghana, 2015)
Introduction: HIV and AIDS related stigmatization and discrimination has severe consequences on HIV and AIDS prevention and interventions, People Living with HIV and AIDS and the spread of the HIV. Objectives: This research aims at determining the level of stigma and discrimination and comprehensive HIV and AIDS Knowledge in the Jaman North District of the Brong Ahafo Region. The study also aims at determining the factors associated with of Stigma and discrimination. Methodology: An analytical cross-sectional study was conducted on three hundred and eighty-four (384) respondents in the Jaman North district of the Brong Ahafo Region. Respondents included males (191) and females (193) above the age of seventeen (17) years in four communities of the district namely Sampa, Goka, Duadaso No.2 and Suma Ahenkro. A multistage and systematic random sampling technique was employed to carry out this research. Due to financial and time constraints four (4) communities in the district were selected. Each of the four communities was divided into four clusters. One cluster was randomly selected and the number of houses listed. Based on the sample size allocated to this community a systematic random approach was used to select houses with not more than two respondents per household. A structured questionnaire based on the USAID tool for measuring stigma and discrimination was modified to obtain information about knowledge on HIV, stigmatizing and discriminatory attitudes. An HIV and AIDS stigma and discriminatory index was then constructed and used to determine the level of stigmatization and discrimination in the district. All ethical issues were strictly adhered to, to ensure confidentiality and anonymity of respondents. Conclusion: The study showed a high level of stigma and discrimination in the Jaman North district (95%) and low knowledge on HIV and AIDS (18%).Females (98.45%) were found to have more stigmatizing and discriminatory attitudes towards PLHIV than males( 92.15%) .This therefore, requires that more efforts be made to educate people in the district about HIV and AIDS and reduce stigma and discrimination.
Thesis (MPh) - University of Ghana, 2015